Preoperative Bevacizumab Does Not Significantly Increase Postoperative Complication Rates in Patients Undergoing Hepatic Surgery for Colorectal Cancer Liver Metastases - Kesmodel, Susan (2008)
Purpose Although bevacizumab (BV) increases survival rates when used with chemotherapy (CTX) in patients who have metastatic colorectal cancer (CRC), an increase in wound complications has been observed in patients who undergo surgery while receiving BV. We therefore evaluated whether neoadjuvant BV is associated with an increase in postoperative complications in patients undergoing surgery for CRC liver metastases. Patients and Methods Two subgroups of patients who received neoadjuvant CTX + BV (n = 81) or CTX alone (n = 44) were identified from a database of patients who underwent surgery for CRC liver metastases. Univariate and multivariate logistic regression models were used to evaluate the association of patient and tumor characteristics, neoadjuvant therapy, and operative factors with postoperative complications. Results Postoperative complications developed in 40 patients (49%) who received CTX + BV and 19 patients (43%) who received CTX. The median time from BV discontinuation to surgery was 58 days (range, 31 to 117 days). No significant associations were identified between BV use and timing of BV discontinuation and postoperative complications. On multivariate analysis, lower serum albumin and concomitant surgical procedures were associated with an increased risk of developing any complication (P = .035 and .023, respectively), and lower serum albumin was associated with hepatobiliary complications (P = .016). Conclusion Neither the use of BV nor timing of BV administration was associated with an increase in complication rates. These data suggest that the combination of BV with neoadjuvant CTX in patients who have CRC liver metastases does not increase surgical complications. To determine the optimal timing of surgery in patients receiving neoadjuvant BV, confirmatory prospective studies are required.